Fashion houses in Rio de Janeiro from the first half of the XIX: property rights and gender - Reis, Laura Junqueira de Mello (2021)
The purpose of this paper is to understand, through fashion houses and 19th centurydressmakers, the relationship between white women, property rights and women’s workin Rio de Janeiro in the first half of the 19th century. From 1816 onwards, a series of Frenchdressmakers and seamstress arrived in Brazil, causing an innovation in terms of Brazilianbusiness and fashion. These French women, as well as some Brazilian women, openedestablishments and established their stores on the outskirts of the famous Rua do Ouvidor.However, not all women had the right to open a business, married women were denied theright to own property; in this sense, we aim to problematize the notion of women owners andtheir civil status and the way they were structuring their businesses in the Brazilian court,making the business related to clothing arousing the interest of society and becoming moreand more inserted in the economic and social logistics of the period.